Gut microbiota dysbiosis affects the local renin-angiotensin system to induce osteoporosis - Zhong, Kai; Wang, Yuanhui; Han, Pengkun; Huang, Zhanwen; Xie, Zonghui; Yu, Peigeng; Liu, Hanwen; Hu, Hao; Tan, Meiyun; Guo, Xing (Frontiers in Endocrinology, 2025)
IntroductionThe gut microbiota has been found to play a key role in bone metabolism, and renin-angiotensin components are locally expressed in bones and affect bone metabolism, but the link between the two is still unclear. This study aims to investigate whether gut microbiota dysbiosis causes osteoporosis through local renin-angiotensin system (RAS).MethodsOsteoporosis was induced in mice by long-term antibiotic feeding, which disrupted their gut microbiota. Subsequently, the role of RAS in this process was investigated by modulating angiotensin II receptor activity.ResultsLong-term antibiotic treatment leads to significant alterations in gut microbiota and leads to osteoporosis, and that localized RAS in bone tissue promotes osteoclast proliferation and activity through up-regulation of ERK1/2 to promote RANKL release and inflammatory infiltration, leading to osteoporosis, and that the angiotensin II Type 2 Receptor (AT2R) may be an important target for this process.ConclusionsDysbiosis of the gut microbiota leads to osteoporosis by enhancing the activity of the local renin-angiotensin system in bones. Upregulation of ERK1/2 and RANKL, along with inflammatory responses, collectively drive bone loss. AT2R may be a potential therapeutic target. These findings highlight the role of the gut-bone axis and suggest that targeted therapeutic approaches should be further investigated.